Clinical impact of T cells, B cells and the PD-1/PD-L1 pathway in muscle invasive bladder cancer: a comparative study of transurethral resection and cystectomy specimens. (2nd November 2019) - Wahlin, Sara; Nodin, Björn; Leandersson, Karin; Boman, Karolina; Jirström, Karin
ABSTRACT: In patients with muscle invasive bladder cancer (MIBC), neoadjuvant chemotherapy (NAC) prior to radical cystectomy has improved survival but there is an urgent unmet need to identify prognostic and predictive biomarkers to stratify patients who will benefit from treatment. This study aimed to examine the composition of tumor-infiltrating immune cells in MIBC, with particular reference to the clinical outcome and the potential modifying effect of NAC. To this end, the expression of CD8 + and FoxP3 + T cells, CD20 + B cells, PD-1 + and PD-L1 + immune cells and PD-L1 + tumor cells was evaluated by immunohistochemistry on tissue microarrays with paired transurethral resection (TURB) specimens, cystectomy specimens and lymph node metastases from 145 patients, 65 of whom had received NAC. Kaplan–Meier and Cox regression analyses were applied to assess the impact of investigated cell subsets on time to recurrence (TTR). In cystectomy specimens, high infiltration of the investigated immune cell populations, but not PD-L1 + tumor cells, were independently associated with a prolonged TTR, whereas in TURB specimens, this association was only seen for CD8 + lymphocytes. An additive beneficial prognostic effect of NAC was seen for the majority of the cell subsets but there was no significant interaction between any immune marker and NAC in relation to TTR. Furthermore, no differences in cell densities prior to NAC treatment were observed between complete and non-complete responders, or pre- and posttreatment in non-complete responders. In conclusion, immune cell infiltration provides important prognostic information in both pre- and postsurgical samples of MIBC, independently of NAC.